Modeling of Photovoltaic Power Generation Systems Considering High- and Low-Voltage Fault Ride-Through - Xu, Xian; Han, Hualing; LI, Haifeng; Zhou, Wenjun; Li, Jie; Chen, Ning (Frontiers in Energy Research, 2022)
The photovoltaic power station has a good development prospect because it can realize concentrated and efficient utilization of solar energy. Considering the detail model of the photovoltaic power station has a power electronic device with a high-frequency switching characteristic, it is not suitable for electromagnetic transient analysis of a large photovoltaic power plant. To solve this problem, this study proposes a simplified model, average model, which uses a controlled current source to replace the power electronic converter and analyzes application backgrounds, advantages, and disadvantages of two models. Then, the control circuit of the average model is improved to switch the control mode by itself when the high- and low-voltage fault occur in the system to make sure the high- and low-voltage ride-through can be completed successfully. Finally, the correctness and effectiveness of the improved average model are verified by simulation.